Α-FeOOH nanowires loaded on carbon paper anodes improve the performance of microbial fuel cells. (June 2021) - Xian, Jiali; Ma, Hua; Li, Zhe; Ding, Chenchen; Liu, Yan; Yang, Jixiang; Cui, Fuyi
Abstract: Nanowires synthesized from metal oxides exhibit better conductivity than nanoparticles due to their greater aspect ratio which means that they can transmit electrons over longer distances; in addition, they are also more widely available than pili because their synthesis is not affected by the bacteria themselves. However, there is still little research on the application of metal oxides nanowires to enhance power generation of microbial fuel cells (MFC). In this study, a simple hydrothermal synthesis method was adopted to synthesize α-FeOOH nanowires on carbon paper (α-FeOOH-NWs), which serve as an anode to explore the mechanism of power generation enhancement of MFC. Characterization results reveal α-FeOOH-NWs on carbon paper are approximately 30–50 nm in diameter, with goethite structure. Electrochemical test results indicate that α-FeOOH nanowires could enhance the electrochemical activity of carbon paper and reduce the electron transfer resistance (Rct ). Furthermore, α-FeOOH-NWs made the power density of MFC 3.2 times of the control device. SEM result demonstrates that nanowires are beneficial to the formation of biofilms and increase biomass on the electrode surface. Our results demonstrate that nanowires not only improve the electrochemical activity and conductivity of carbon paper but also facilitate the formation of biofilms and increase the biomass of the anode surface. These two mechanisms work together to boost extracellular electron transfer and power generation efficiency of MFC with α-FeOOH-NWs. Our study provides further evidence for the electrical conductivity of metal nanowires, promoting their potential applications in electricity generation such as MFC or other energy development fields. Highlights: α-FeOOH nanowires enhanced electron transfer rate and reduced Rct. α-FeOOH nanowires are beneficial to the formation of biofilms. α-FeOOH nanowires made the power density of MFC 3.2 times than the control.